Bibliometric Analysis of the Development Map and Research Trends in Qur’anic Studies and Tafseer: A Scopus Database Exploration (1974-2023) - Ayuni, Windi; Nirwana, Andri; Nurrohim, Ahmad (UIN Syarif Hidayatullah Jakarta, 2023)
The research employs a bibliometric approach using R and Rstudio tools, VosViewer, and Microsoft Excel to evaluate the growth of Qur'anic Studies and Tafsir research papers. The sample of reference articles, totaling 1,476 articles, is sourced from the Scopus database using Boolean operators. Further research is still within the scope of Qur'anic Studies through Tafsir Science. The research conducted a data search on 23 November 2023 using Scopus as a guide, using the title and abstract of the article to search for keywords related to Qur'anic Studies and Tafsir.The search results reveal 904 publications published between 1974 and 2023, involving 1807 authors, 372 single authors, and 8.739% international co-authors. These publications have been cited 35,873 times and have an average citation per publication of 4,061. The number of publications integrating Qur'anic Science and Tafsir has fluctuated over the past 12 years, increasing from 2017-2023. The number of publications has increased from 49 in 2017 to 59 in 2018, 69 in 2019, 85 in 2020, 100 in 2021, 110 in 2022, and 120 in 2023. This indicates potential research opportunities for Qur'anic Science and Tafsir.